STAKEHOLDER VIEWS ON SUSTAINABLE COMMUNITY-BASED ECOTOURISM: A CASE OF THE PAGA CROCODILE PONDS IN GHANA - Rapael Ane ATANGA (Geo Journal of Tourism and Geosites, 2019)
This study analysed tourism at the Paga Crocodile Ponds in the Upper East Region of Ghana as a basis to evaluate its potential for sustainable community-based ecotourism development. The study employed qualitative case study approach, using data from secondary and primary sources that involved in-depth interviews with key actors in the tourism sector of the community in Ghana. Results of the study suggest that tourism in the community is in its developing stage. The Paga Crocodile Ponds attract international and domestic tourists, and tourism influences the socio-cultural, economic, and environmental livelihood of the community. The research found that the ponds were silted and experiencing threats of drought and competition from other uses of the water. Tourism at Paga is mainly managed by the traditional community leaders with insufficient tourism infrastructure and therefore needs support from government and other stakeholders. The results suggest that a sustainable community-based ecotourism development in the community require improvement in stakeholder involvement, environmental sanitation and water level of the ponds.